Understanding the peroxisome proliferator-activated receptor gamma (PPAR-γ) role in periodontitis and diabetes mellitus: A molecular perspective - Nicchio, Ingra Gagno [UNESP] (2025)
Periodontitis and Type 2 Diabetes Mellitus (T2DM) are chronic conditions with dysregulated immune responses. Periodontitis involves immune dysfunction and dysbiotic biofilms, leading to tissue destruction. T2DM is marked by insulin resistance and systemic inflammation, driving metabolic and tissue damage. Both conditions share activation of key pathways, including Nuclear Factor Kappa B (NF-κB), Activator Protein-1 (AP-1), and Signal Transducer and Activator of Transcription (STAT) proteins, reinforcing an inflammatory feedback loop. This review highlights the role of Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ), a transcription factor central to lipid and glucose metabolism, adipogenesis, and immune regulation. PPAR-γ activation has been shown to suppress inflammatory mediators such as Tumor Necrosis Factor Alpha (TNF-α) and Interleukin 6 (IL-6) through the inhibition of NF-κB, AP-1, and STAT pathways, thereby potentially disrupting the inflammatory-metabolic cycle that drives both diseases. PPAR-γ agonists, including thiazolidinediones (TZDs) and endogenous ligands such as 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2), show promise in reducing inflammation and improving insulin sensitivity, but they are limited by adverse effects. Therapies, including Selective Peroxisome Proliferator-Activated Receptor Modulators (SPPARMs), have been developed to offer a more targeted approach, allowing for selective modulation of PPAR-γ activity to retain its anti-inflammatory benefits while minimizing their side effects. By integrating insights into PPAR-γ’s molecular mechanisms, this review underscores its therapeutic potential in mitigating inflammation and enhancing metabolic control.